Changes in saccadic eye movement and smooth pursuit gain in patients with acquired comitant esotropia after strabismus surgery - Miharu Mihara; Atsushi Hayashi; Ken Kakeue; Ryoi Tamura (Journal of Eye Movement Research, 2023)
This study investigates the change in horizontal saccadic eye movement and smooth pursuit in patients with acquired comitant esotropia (ACE), before and after strabismus surgery. The horizontal saccades and pursuit in 11 patients with ACE were recorded using a video eye-tracker under binocular viewing before and after strabismus surgery. Participants were instructed to fixate on the new target as rapidly as possible when it randomly appeared at either 18.3° rightward or 18.3° leftward. For smooth pursuit, participants were asked to track, as accurately as possible, a step-ramp target moving at ±6.1°/s. The asymmetry of adduction-abduction and the binocular coordination in gains of saccade and pursuit were compared between the pre- and post-surgical data. The asymmetry of adduction-abduction saccade gain in each eye after surgery tended to be smaller than that before surgery. The binocular coordination of saccade showed significant improvement after surgery in only the non-dominant eye direction. Adduction-abduction asymmetry in the smooth pursuit gain in each eye after surgery tended to be smaller than before surgery. After surgery, the binocular coordination of pursuit was improved significantly in both directions. In patients with ACE, binocular coordination of saccade and smooth pursuit was poor. Binocular coordination of saccade and pursuit seems to be improved due to the improvement in ocular deviation angle and binocular visual function after surgery.